A Smart Home Architecture Based on Resource Name Service - Cui Yang; Bo Yuan; Ye Tian; Zongming Feng; Wei Mao (2014 IEEE 17th International Conference on Computational Science and Engineering, 2014)
Smart home contains centralized controlled lights, Heating, Ventilation and Air Conditioning (HVAC), appliances, security locks of gates and doors and other intelligent equipment, to provide convenient, comfortable, energy efficient and secure services to users. Although many countries and organizations have designed various smart home architectures, there are still some problems in these existing solutions. One problem is the interoperability among multiple appliances in home environment. Another rising problem is the difference of identifiers, operating platform and programming languages accepted for smart home systems. Heterogeneous services and devices need to be interoperable each other in order to perform joint execution of tasks. Therefore, the heterogeneity problem of appliance and identifier leads to poor compatibility in smart home systems. This paper proposes a novel smart home architecture based on Resource Name Service (RNS), which defines the participating parties of smart home and the relationships between them, and designs the specific process of smart home services. This architecture can achieve interoperability among various vendors and improve the compatibility without doing much extra changes on these existing smart home appliances.